Bridging gaps in healthcare: child health services and specialist care collaboration for young children with autism and coexisting conditions - Nygren, Gudrun; Gillberg, Christopher; Carlsson, Emilia (Frontiers in Pediatrics, 2025)
AimThis study aimed to evaluate a clinical project aiming to address gaps in healthcare for young children in an immigrant, low-resource district from early identification of regulatory problems, autism, and other neurodevelopmental symptoms by child health services to assessment and interventions in specialist care.MethodsA mixed-model design was employed, consisting of a description of the clinical project and data from healthcare statistics to evaluating the care chain. Qualitative in-depth interviews were conducted to capture the perspectives of participating child health nurses. Data were analyzed using content analysis.ResultsThe mean age for referral from primary to specialist care for suspected autism decreased from 38 to 27 months at (n = 59). A total of 55 children were diagnosed with autism. The mean age at autism diagnosis decreased from 44 to 31 months. Waiting times from referral to intervention were shortened. Interventions were already initiated in primary care at the time of referral. Qualitative analyses of nurse experiences revealed three main categories: (1) new and increased knowledge, (2) great importance for every child and family, and (3) an efficient method with fewer gaps, which holds further potential for development.ConclusionProfessionals’ increased knowledge of early symptoms in children, combined with novel healthcare methods for close collaboration, made it possible to bridge the gaps and provide young children and their families with early assessments and essential early interventions. The study results point to opportunities for integrated healthcare and collaboration with families and preschools.